From Heritage to Sustainability: The Future of the Past in the Hot Arid Climate of the UAE - Salameh, Muna (2023)
Achieving future energy objectives and promoting social, economic, and environmental sustainability can be inspired by heritage and historic structures, which make up a sizeable component of the existing building industry. Heritage architecture and urban sites are known for their capability of positive interaction with the climate to provide better thermal conditions, beside their capability of strengthening cultural identity and improving the economic sector for the related sites. Thus, the main purpose of this research is to highlight the positive sustainable effects (social, economic and environmental) for a proposal of conserving and reconstructing a vernacular heritage architecture site in the hot arid climate in the UAE. The research used a qualitative methodology based on multicriteria descriptive schemes beside ENVI-met software. The research’s findings presented the capability of the conserved heritage area to strengthen the social and cultural identity and improve the economic sector. Moreover, the results demonstrated that the conserved heritage district had a better microclimate and predicted mean vote for outdoor thermal comfort compared to the basic case heritage district prior to rehabilitation and another modern district. The conclusion promotes heritage conservation in hot arid climates and encourages the preservation of vernacular architecture and traditional sites to achieve the sustainable goals for creating sustainable cities that can mitigate climate change.